IMPROVING STUDENTS’ WRITING SKILL OF DESCRIPTIVE TEXT BY USING PICTURE OF THE STUDENTS XI-AKL AT SMK JAGAKARSA JAKARTA IN THE ACADEMIC YEAR OF 2022/2023 - Mastiara, Puri; Wahdini, Lili; Gunawan Susandi, Deny (Jurnal Impresi Indonesia, 2023)
This research aims to improve students' descriptive text-writing skills by using pictures. The subjects of this research are the students of SMK Jagakarsa, Jakarta, academic year 2022/2023, which consist of 21 students in the XI-AKL grade (7 boys and 14 girls). This research was conducted by using classroom action research. The method that is used in this research is quantitative. The researcher used observation, tests, and documentation for the collection of data instruments. This research was accomplished in two cycles, with every cycle comprising two tests. In the pre-test on the first cycle, the teacher gave the questions before treatment; then, in the post-test I, the researcher gave the treatment based on the descriptive text material. In the post-test on the second cycle, the researcher gave more treatment and information about descriptive text writing skills by using pictures as learning media. The result of this research showed that there was an increase in students' writing skills in descriptive text. In the first test as a pre-test, the students got scores?75, 15 out of 21 students (71,42%). In the second test, as a cycle I post-test, the students scored scores?75 were, 9 students out of 21 (42,85%). In the last test, as a post-test of cycle II, the students scored?75, 4 out of 21 students (19,04%). The increase from the cycle I post-test to the cycle II post-test was about 28,57%. The total increase of the student's scores from the pre-test to the post-test of cycle II (two) was 54,38%. In other words, the student's writing skills in descriptive text using pictures improved and went well from the first to the next.